Apakah Peningkatan Risiko Likuiditas, Risiko Kredit, dan Risiko Suku Bunga Berdampak Terhadap Profitabilitas Bank? - Allifiyani H; Rinda Siaga Pangestuti (Ekonomis: Journal of Economics and Business, 2021)
Banking performance has decreased on average in terms of credit quality, liquidity, ability to generate net interest income, and profitability in the last two years. This indicates an increase in credit risk, liquidity risk, interest rate risk, and bank profitability risk. This study contributes in providing an explanation regarding banking performance which can lead to a decline in profitability that can influence investment decision making by investors in terms of the performance of the issuer. This research is included in the category of quantitative research with a sample of commercial banks in Indonesia selected based on purposive sampling method. The results of this study indicate that the lower the credit risk the higher the bank's profitability, the higher the interest rate risk the higher the bank's profitability, and the liquidity risk which has a significant positive effect on the performance of banks listed on the Indonesia Stock Exchange in the 2016-2018 period.